Biocontrol of grey mould disease on grape caused by botrytis cinerea with autochthonous wine yeasts - Raspor, Peter; Miklic-Milek, Damjana; Avbelj, Ma; Cadez, Neza (Food technology and biotechnology, 2010)
Biocontrol activities of different yeast species and strains isolated from grape/must/ wine environments have been compared to those of commercially available antagonistic yeast species of Candida oleophila. A total of 591 yeast isolates were tested in a preliminary screening on agar to select isolates showing inhibitory effect against Botrytis cinerea, the plant pathogen causing grey mould disease on grape. Yeast species Aureobasidium pullulans, Metschnikowia pulcherrima and Pichia guilliermondii showed, on average, higher biocontrol activity than commercially used yeast Candida oleophila. Furthermore, these three species and Saccharomyces cerevisiae, which is potentially interesting biocontrol agent against grey mould of grapes, were selected for their inhibitory effects and assayed in vitro on different solid synthetic media for their antagonistic capacity towards B. cinerea. The results indicate that the composition of the medium had an impact on the biocontrol activity of yeast species and strains, as Saccharomyces cerevisiae showed the highest antagonistic activity against B. cinerea when tested on media with increased concentrations of glucose. The antagonistic activity of selected yeast strains was finally determined on wounded and sound grape berries of cultivars Rebula and Chardonnay for their ability to inhibit infection by B. cinerea moulds. Results suggest that antagonist yeasts with the potential to control B. cinerea on grape can be found among the microflora associated with the berries. Key words: biocontrol agents, Botrytis cinerea, grey mould, antagonism, grapes, wine yeasts